JAVANESE ADJECTIVE INTENSIFIER DIPHTHONG IN PONOROGO: GENERATIVE TRANSFORMATIONAL PHONOLOGY STUDY - Kusuma, Invandri; Anam, Moh Khoirul (English Department FBS UNP, 2019)
Intensifying words commonly use word like very, absolutely, etc. However, Javanese people not only use the words but also change the sound of the word. This study aims to examine the diphthong pattern of the adjective intensifier in Javanese in Ponorogo. The pattern was examined using the Transformational Generative Phonology to describe the phonological rules of adjective intensifiers. The number of the data was 65 of the most commonly used adjective words. When collecting data, the techniques used were random sampling by taking 35 informants from five districts in Ponorogo. The literature and note-taking technique functions to document the speech of the speaker, while to analyze the data the distributional method is used. The results of the study found that the patterns of diphthong sound are [ua], [uÉ™], [ue], [uÉ›], [uo], [uÉ”], [ui] and [É”u]. The diphthongs are divided into three types based on the classification of basic vocal sounds that undergo phonological changes, namely ascending, centering and descending. The vowel phoneme /u/ becomes the underlying to express the 'intensifying' nature into all the vowels afterwards, while the allophonic vowel [É”] is more accepted as variations of the phoneme /u/ to 'intensify' when appearing before the sound [u] because they have the distinctive features [Î± back] and [Î² round]. This study also revealed that sound insertion happened only in the first syllable of a word.Â Keywords:Â Javanese Language, transformational generative, diphtong, adjective